Curriculum development : the structuring of vocational knowledge for degree purposes. - Hewson, Daryl (My University, 2011)
In the context of the hospitality sector developing a more academic identity in South Africa, this research study explores the relationship between theoretical and practical knowledge forms in the development of a degree in hospitality management. The study aimed to establish what value culinary knowledge would have within an academic degree in hospitality management and what the relation between theory and practical knowledge within a Culinary Studies module could be. Semi-structured interviews were used to explore the views of hospitality sector representatives in Higher Education and the Hospitality Industry on the selection and organisation of culinary knowledge within a degree in hospitality management. The data was analysed both qualitatively and quantitatively, using Jeanne‘s Gamble‘s model of knowledge forms (Gamble, 2004) as the main analytical tool. The findings revealed an undisputed need for vocational culinary knowledge within a degree in hospitality management qualification. In addition, there emerged a method for how the interdependence between theoretical and practical knowledge forms within the qualification can be described and quantified. This is a possible precedent for analysing other fields of knowledge within a degree in hospitality management. Through this analysis of culinary knowledge, the research study provided a greater understanding of how an analysis of knowledge forms can inform the overall selection and organisation of knowledge across a qualification in hospitality management.